The Role of Green Bureaucracy in Advancing Food Policy Innovation amid Global Crises - Siti Marwiyah; Muslimatul Firdaus; Pjakbarulys Pjakbarulys; Diah Retno Oktaviana; Juliant Nabicha Sapnuar Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Global crises in recent years have transformed the paradigms of public governance and global food systems. The COVID-19 pandemic, the Russia–Ukraine geopolitical conflict, climate change, global inflation, and disruptions in international supply chains have become major factors affecting food stability in many countries, including Indonesia. These conditions require bureaucratic institutions not only to perform administrative functions but also to establish adaptive, innovative, and environmentally sustainable governance systems. This study aims to analyze the concepts of green bureaucracy and food policy innovation in responding to the era of global crises from the perspectives of public administration and sustainable governance. The research employed a descriptive qualitative approach based on a literature review. Data were obtained from Scopus-indexed international journals, Google Scholar publications, scientific articles, reports from international organizations, and government policy documents. The findings indicate that green bureaucracy has emerged as a new paradigm in modern public administration reform, emphasizing the integration of sustainability principles, resource efficiency, governance digitalization, and multi-stakeholder collaboration in national food management. Food policy innovation is manifested through agricultural digitalization, the strengthening of local food systems, the protection of agricultural land, the enhancement of national food reserves, and the development of data-driven food governance. The study also reveals that the major challenges to implementing green bureaucracy in Indonesia include institutional fragmentation, weak cross-sectoral coordination, dependence on global markets, and limited bureaucratic capacity at the local government level. Therefore, bureaucracy reform based on green governance is a crucial strategy for creating a resilient, inclusive, and sustainable national food system amid the dynamics of global crises.